Congenital spindle cell rhabdomyosarcoma: An international cooperative analysis - Whittle, Sarah; Venkatramani, Rajkumar; Schönstein, Anton; Pack, Svetlana D.; Alaggio, Rita; Vokuhl, Christian; Rudzinski, Erin R.; Wulf, Anna-Lena; Zin, Angelica; Gruver, Juliana R.; Arnold, Michael A.; Merks, Johannes H. M.; et al. (European journal of cancer, 2022)
Background - Spindle cell rhabdomyosarcoma (RMS) is a rare variant of RMS accounting for up to 10% of cases in infants. In older children and adults, spindle cell RMS is associated with MYOD1 mutations and a poor prognosis. In infants, it is associated with recurring fusions involving NCOA2 and VGLL2. Reports in the literature suggest a favorable prognosis for this subset, however, little is known about treatment and outcome data of infants with spindle cell RMS. - Methods - Characteristics, treatment, and outcome of an international cohort of 40 patients aged ≤ 12 months with spindle cell RMS treated from 1997 to 2018 were evaluated. - Results - Localized disease (LD) was diagnosed in 39 patients. The median age at diagnosis was 2.5 months (range 0-12 months). Expert pathologic review confirmed the diagnosis of spindle cell RMS in all patients. Among 26 tumors that had molecular evaluation, 13 had rearrangements of NCOA and/or VGLL. Multimodal treatment of infants with LD included conventional (age adjusted) chemotherapy (n = 37), resection (n = 31) and radiotherapy (RT) (n = 5, brachytherapy in 3). Complete remission was achieved in 37/39 patients. Progressive disease occurred in two infants, relapsed disease in three. Microscopically complete surgical resection was associated with five-year event-free survival (EFS) and overall survival (OS) of 100%. Two patients with tumors ≤ 5 cm were treated with microscopically complete resection only and were alive 1 and 4.2 years after diagnosis. The 5-year EFS and OS for infants with LD were 86% (±11; CI 95%) and 91% (±9; CI 95%), respectively. One patient had metastatic disease (NCOA fusion positive) with primary tumor in head and neck and brain metastases. This patient died despite chemotherapy and delayed resection of the primary tumor due to respiratory failure secondary to cytomegalovirus infection 1.2 years after diagnosis. - Conclusion - Infants with spindle cell RMS have an excellent prognosis. Multimodal treatment including microscopically complete resection of the tumor is strongly recommended.